Design of a Motor Vehicle Exhaust Noise Intensity Measurement System to Determine Driving Standardization Levels Based on the Internet of Things (IoT) - Muhammad - Rizky (JURNAL KAJIAN TEKNIK MESIN, 2025)
The problem of high-intensity noise, both in urban and rural areas, needs to be addressed immediately as it disrupts the balance between humans and the environment. One major source of noise pollution is vehicle exhaust that does not comply with standards, thus violating regulations. According to the Regulation of the Minister of Environment and Forestry No. 56 of 2019, the maximum noise limits are set at 74 dB for cars, 84 dB for freight vehicles, and 82 dB for motorcycles. Therefore, an Internet of Things (IoT)-based vehicle sound intensity measurement system is needed, utilizing a Sound Level Meter (SLM) in decibels (dB). The system is designed in a box equipped with sound sensors and a camera to measure noise levels in real-time and provide notifications when thresholds are exceeded. With an Arduino microcontroller as the main controller, the device can be monitored remotely via a smartphone. This system is expected to improve the efficiency of vehicle noise monitoring, support the creation of a healthier environment, and increase public awareness of complying with exhaust noise standards